Synchrotron Radiation and Nanotechnology for Stem Cell Research - Giuliani, Alessandra; Fiori, Fabrizio; Manescu, Adrian; Komlev, Vladimir S.; Renghini, Chiara; Rustichelli, Franco (IntechOpen, 2011)
None